Non-Operative Management of Traumatic Gallbladder Bleeding with Cystic Artery Injury: A Case Report - Tae Hoon Kim (Journal of Trauma and Injury)
Gallbladder injuries are rare in cases of blunt abdominal trauma and are usually associated with damage to other internal organs. If the physician does not suspect gallbladder injury and check imaging studies carefully, it may be difficult to distinguish a gallbladder injury from gallbladder stone, hematoma, or bleeding. Therefore, in order not to miss the diagnosis, the clinical findings and correlation should be confirmed. In the present case, a 60-year-old male presented to a local trauma center complaining of pain in the upper right quadrant and chest wall following a motor vehicle collision. Abdominal computed tomography (CT) showed a hepatic laceration and hematoma in the parenchyma in segments 4, 5, and 6 and active bleeding in the lumen of the gallbladder. Traumatic gallbladder injuries generally require surgery, but in this case, non-operative management was possible with cautious follow-up consisting of abdominal CT and angiography with repeated physical examinations and hemodynamic monitoring in the intensive care unit.